Lamar archaeology : Mississippian chiefdoms in the deep South - Williams, J. Mark; Shapiro, Gary (University of Alabama Press, 1990)
A Dan Josselyn Memorial Publication Lamar Archaeology provides a comprehensive and detailed review of our knowledge of the late prehistoric Indian societies in the Southern Appalachian area and its peripheries. These Lamar societies were chiefdom-level groups who built most of the mounds in this large region and were ancestors of later tribes, including the Creeks and Cherokees. This book begins with a history of the last 50 years of archaeological and historical research and brings together for the first time all the available data on this early culture.